DIGITALISATION OF WORK PROCESSES IN THE NIGERIAN UNIVERSITY SYSTEM UNDER THE NEW NORMAL - Otto, Dorcas D.; Ukpere, Wilfred; Adekanmbi, Foluso (Annals of Spiru Haret University. Economic Series, 2023)
The global spread of the coronavirus (COVID-19) has left a world with changing work situations in its trail. What started as some innovative electronic processes (e-processes) to enhance workflow and ensure effective service delivery in the Nigerian University System (NUS) gained momentum during the COVID-19 period and has opened new and bright opportunities for e-processes in the aftermath of COVID-19. However, inspite of the numerous advantages of a progressive digitalisation of work processes in the NUS, the perceived challenge has been that of mixed reactions from the workforce. While a few of the workforce appear to be equipped and favourably disposed to the new normal, a larger proportion seem unprepared and somewhat apathetic to the present demands for a 21st Century efficient and effective service delivery methods in the NUS. The objective of the paper is to appraise the introduction, benefits and challenges of e-processes in the NUS especially in post COVID-19 era. It relied on primary (participant observation) and secondary (documents) sources of data and was guided by the Innovation Diffusion Theory. The paper explored critical issues of e-processes and result-oriented management under the new normal in the NUS and made appropriate recommendations for both management and staff. In view of its flexibility and benefits, the paper concludes that, so far, digitalisation of work processes in the NUS has expanded the speed and efficiency of processing documents, thereby, enhancing the welfare of stakeholders